Spatial and depth distribution of salinity and nitrate in a depleted alluvial aquifer (Haouz plain, Morocco) - Hamza Sahraoui; Younes Fakir; Houssne Bouimouass; Sarah Tweed; Marc Leblanc; Rabia Benaddi; Abdelghani Chehbouni (Journal of Hydrology: Regional Studies)
Understanding groundwater contamination processes in depleted aquifers is needed to improve their integrated management. The present study aims to understand how the conditions prevailing in a depleting detritic unconfined aquifer could affect the salinity and nitrate contamination. The depletion has caused a shift in our alluvial aquifer from dominant very shallow groundwater (< 20 m) in the 1970s to dominant deep groundwater (> 40 m) currently. It was found that (i) groundwater was moderately affected by salinity and nitrate, (ii) the dominant hydrochemical factors are rock weathering, halite dissolution, and reverse ion exchange, and (iii) the nitrate contamination is higher in shallow groundwater but it was detected at all depths. The thick unsaturated zone, which has developed because of the decline of the water table, would have mitigated the surface-borne contamination and reduced the direct effects of evapotranspiration. Using tritium as age indicator, it was suggested that nitrate in deep groundwater could originate from a historical use of fertilizers. In addition, vertical flows induced by decreasing water-table from pumping could transport younger groundwater with high loads of nitrate to mix with older deep groundwater with low nitrate. Serious problems could arise from further mobilization of salts by pumping deep groundwater and from the effects of downward movement of contaminants accumulated in the thick unsaturated zone after sufficient migration time or increases in groundwater recharge rates.